Cratering studies in Polyvinylidene Fluoride (PVDF) thin films - Shu, Anthony; Bugiel, Sebastian; Grün, Eberhard; Hillier, Jon; Horányi, Mihály; Munsat, Tobin; Srama, Ralf (Planetary and space science, 2013)
Thin, permanently polarized Polyvinylidene Fluoride (PVDF) films have been used as dust detectors on a number of missions including the Dust Counter and Mass Analyzer (DUCMA) instrument on Vega 1 and 2 to comet 1P/Halley, the High Rate Detector (HRD) on the Cassini Mission to Saturn, the Student Dust Counter (SDC) on New Horizons to Pluto, the Dust Flux Monitor Instrument (DFMI) on the Stardust mission to comet 81P/Wild 2, the Space Dust (SPADUS) instrument on the Earth orbiting Advanced Research and Global Observation Satellite (ARGOS) and the Cosmic Dust Experiment (CDE) on the Aeronomy of Ice in the Mesosphere (AIM) mission in orbit around the Earth. Due to their low power requirements and light weight, large surface area detectors can be built for observing low dust fluxes. The operation principle behind metal-coated PVDF detectors is that a micrometeorite impact removes a portion of the metal surface layer, exposing the permanently polarized PVDF dielectric underneath. This changes the local electric potential near the crater, and the surface charge of the metal layer, which can be recorded as a transient current. The dimensions of the crater determine the strength of the potential change and thus the signal generated by the PVDF. Currently used scaling laws relating impactor parameters to crater geometry, which are used to predict PVDF response, are suspected to have systematic errors. Work is being undertaken to develop a new crater diameter scaling law using iron particles in PVDF. Cratered samples are analyzed using a 3D reconstruction technique using stereo image pairs taken in a Scanning Electron Microscope (SEM) and cross sections taken in a Focused Ion Beam (FIB). We report on the details of the reconstruction techniques and the initial findings of the crater parameter scaling law study.